PENGARUH INVESTASI TERHADAP PENYERAPAN TENAGA KERJA - Rastri Paramita; Ratna Christianingrum (Pusat Kajian Anggaran, 2017)
This paper aims to analyze the effect of investment, source of capital, number of projects, and sector towards labour. Type of data in this paper is pannel and secodary data. The study used data period from 2012 until 2016. The estimation methods is a multiple regression. The result shows that investment has significant effect on labour absorptiont. Every Rp1 trillion investment can absorb 621 workers. Investment in food and plantation crop sector having the highest employment absorb, where every investment in this sector able to absorb 143,320 labour. It takes the government’s policy to create a beneficial investment environment that can enlarge effect of investment towards labour.